2011
DOI: 10.1016/j.otsr.2011.05.017
|View full text |Cite
|
Sign up to set email alerts
|

Forearm reconstruction with bone allograft following tumor excision: A series of 10 patients with a mean follow-up of 10 years

Abstract: A bone allograft when available can be considered as one amongst other suitable options for the reconstruction of the forearm skeleton.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 21 publications
1
29
1
Order By: Relevance
“…The most frequent complications observed in arthroplasties with osteoarticular allografts are joint instability and articular degeneration [16, 17, 1925]. None of the five patients in our series developed any form of instability, but recorded incidences in the literature are quite high.…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…The most frequent complications observed in arthroplasties with osteoarticular allografts are joint instability and articular degeneration [16, 17, 1925]. None of the five patients in our series developed any form of instability, but recorded incidences in the literature are quite high.…”
Section: Discussionmentioning
confidence: 64%
“…Good to excellent functional outcome can be achieved; nevertheless complications are still common. In contrast to allograft reconstructions at other locations, infection is rare in osteoarticular reconstructions of distal radius [5, 16, 17, 1925]. Only Szabo et al [20] observed one minor infection (Table 1) [17, 1922, 24, 25], whilst the incidence of fractures and nonunion reaches up to 25% for both [17, 1922, 24, 25].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Van Isacker et al [18] report in a series of forearm allograft similar results, they found that intercalary allograft had fewer complications than osteoarticular allografts, and they had a better functional MSTS score.…”
Section: Discussionmentioning
confidence: 94%
“…24,26 The metatarsal bone and proximal phalanges used in this study were smaller, and therefore revascularization was satisfactory in 100% of cases in the control group and in 50% of cases in the experimental group, based on the quality of the radiological consolidation.…”
Section: Discussionmentioning
confidence: 85%